2020
DOI: 10.3390/rs12142234
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Mapping of Soil Organic Carbon Using Machine Learning Algorithms in Northern Iran

Abstract: Estimation of the soil organic carbon (SOC) content is of utmost importance in understanding the chemical, physical, and biological functions of the soil. This study proposes machine learning algorithms of support vector machines (SVM), artificial neural networks (ANN), regression tree, random forest (RF), extreme gradient boosting (XGBoost), and conventional deep neural network (DNN) for advancing prediction models of SOC. Models are trained with 1879 composite surface soil samples, and 105 auxiliary data as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 106 publications
4
49
1
1
Order By: Relevance
“…The influence of land use type on SOC prediction and the importance of optical and radar data under different land use types were analyzed. The overall prediction result of the model is better than some existing researches based on satellite remote sensing data [16,21,[23][24][25]33], and is similar to the result of Taghizadeh-Mehrjardi et al [17]. Among the three land use types, the prediction results of orchard (R 2 = 0.86 and MSE = 0.004%) are better than dry land and paddy field.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The influence of land use type on SOC prediction and the importance of optical and radar data under different land use types were analyzed. The overall prediction result of the model is better than some existing researches based on satellite remote sensing data [16,21,[23][24][25]33], and is similar to the result of Taghizadeh-Mehrjardi et al [17]. Among the three land use types, the prediction results of orchard (R 2 = 0.86 and MSE = 0.004%) are better than dry land and paddy field.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, it is necessary to explore the contribution of remote sensing data to SOC prediction. There have been some studies on SOC prediction based on remote sensing data that achieved good prediction results, especially optical data (e.g., Sentinel-2 [15][16][17][18][19][20][21], Landsat [22][23][24][25][26][27][28], and MODIS satellite data [29][30][31]); their bands cover from visible to short-wave infrared, providing more information. However, the application of optical data is susceptible to weather conditions, especially in the Sichuan Basin where clouds occur most frequently [32], so the available optical data are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Gholizadeh, A. et al (2018) showed that GNDVI and SATVI indices provided the strongest correlation with SOC on agricultural plots. Also, several studies conclude that vegetation indices are the most important variables in predicting soil properties (Gopp, N.V. et al 2017;Chen, D. et al 2019;Emadi, M. et al 2020).…”
Section: Remote Sensing Datamentioning
confidence: 99%
“…Soil bulk density is a function of organic matter content [ 26 ]. Organic matter content and NDVI are highly dependent on the natural vegetation cover structure and the plant residue left after plant harvesting [ 111 ]. Therefore, organic matter content vividly explains the link between bulk density and NDVI.…”
Section: Discussionmentioning
confidence: 99%